2014
DOI: 10.1002/ajh.23893
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease as biomarker for optimal biologic dosing of ARAC in patients with acute myeloid leukemia

Abstract: We assessed by flow cytometry minimal residual disease (MRD) in patients with acute myeloid leukemia (AML) given standard-dose (SDAC) and high-dose ARA-C (HDAC) regimens. Of 163 patients enrolled, 130 (median age, 45 years; range, 18-59 years) qualified for analysis, all achieving complete remission after treatment with SDAC (n 5 78) or HDAC (n 5 52) plus etoposide and daunorubicin. Consolidation consisted of intermediate-dose ARA-C and daunorubicin. MRD negativity was significantly more frequent in the SDAC v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…The poor long-term prognosis of standard induction (DA) therapy correlated with the levels of minimal residual disease (MRD) [4] . A high level of MRD was found to correlate with a higher percentage of chemoresistant leukemic stem cells, which are characterized by their inherent ability for self-renewal, in the bone marrow (BM) of AML patients treated with induction therapy [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The poor long-term prognosis of standard induction (DA) therapy correlated with the levels of minimal residual disease (MRD) [4] . A high level of MRD was found to correlate with a higher percentage of chemoresistant leukemic stem cells, which are characterized by their inherent ability for self-renewal, in the bone marrow (BM) of AML patients treated with induction therapy [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…To explore this hypothesis, we carried out a retrospective analysis of 130 patients who achieved an mCR after one cycle of either standard dose (SDAC) or high doses of cytarabine (HDAC). 59 We observed that the SDAC regimen was associated with a greater MRD-negativity frequency. In 178 patients, who achieved CR after intensive induction, the MRD level assessed at days 16–18 after induction, was associated with outcome.…”
Section: Mrd Detection By Mpfcmentioning
confidence: 64%
“…It is of particular importance to identify patients with high risk of relapse and death. While AMLs with positive MRD assessed by flow cytometry are well‐known to have dismal prognosis , the prognosis of MRD negative patients depends on other prognosis factors such as ELN classification, age and leukocytosis.…”
Section: Discussionmentioning
confidence: 99%